2007
DOI: 10.1177/1076029607303341
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Factor V Leiden, Factor V Hong Kong, Factor II G20210A, Methylenetetrahydrofolate Reductase C677T, and A1298C Mutations Related to Turkish Thrombosis Patients

Abstract: most common identified mutations are factor V Leiden (FV Leiden), prothrombin 20210G>A (FII G20210A), methylenetetrahydrofolate reductase 677 C>T (MTHFR C677T), and 1298A>C (MTHFR A1298C) (3-5). FV Leiden and FV Hong Kong mutations of FV gene can render FVa resistant to activated protein C because of a loss of 306 and 506 cleavage sites, respectively (6). FV Leiden predisposes the patient to thrombosis 7 ; however, the FV Hong Kong mutation is a substitution of A>G in the 1090th nucleotide of factor V gene (6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…However, there is no established evidence of significant association between thrombosis and heterozygosity to MTHFR 677C-T. During recent years, increased evidence indicates that this polymorphism, which is very common in the population, is not a risk factor for thrombosis. In fact, an article describing molecular analysis of inherited genetic risk factors in Turkish thrombosis patients has been recently published by Dö lek et al [68] demonstrating no difference between thrombosis patients and control group in regard to MTHFR. Even homozygosity to MTHFR is not considered to be associated with thrombosis when there is no high level of homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no established evidence of significant association between thrombosis and heterozygosity to MTHFR 677C-T. During recent years, increased evidence indicates that this polymorphism, which is very common in the population, is not a risk factor for thrombosis. In fact, an article describing molecular analysis of inherited genetic risk factors in Turkish thrombosis patients has been recently published by Dö lek et al [68] demonstrating no difference between thrombosis patients and control group in regard to MTHFR. Even homozygosity to MTHFR is not considered to be associated with thrombosis when there is no high level of homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…6 Initially, the 677TT genotype was reported to be strongly associated with hyperhomocysteinemia and/or venous thrombotic events, 7-9 but more recent studies, such as ours, question these associations. [10][11][12] One possible explanation for this controversy could be that other genetic determinants of hyperhomocysteinemia may contribute to the elevated Hcy level and thrombosis.…”
mentioning
confidence: 99%
“…In spite of this, the data of Akar et al [18] confirmed that the silent mutation at MTHFR 1317 T-C did not have any effect on the occurrence of DVT neither by itself nor in combination with FV 1691 A. Moreover, in the study by Dolek et al [19], while significant relationship was determined among FVL and thrombosis, and MTHFR C677T was equally distributed in the thrombosis group compared with the healthy group.…”
Section: Discussionmentioning
confidence: 89%